Comparison of Fecal Calprotectin Levels in Iranian general population and army personnel - Azimzadeh, Pedram; Iravani, Shahrokh (Archives of Advances in Biosciences, 2012)
Fecal Calprotectin is released in colon by activated neutrophils. Investigation of diagnostic application of determination of fecal Calprotectin levels is considered by many researchers to compare between different colorectal diseases like Irritable Bowel Syndrome (IBS) and Inflammatory Bowel Diseases (IBD). Due to the effect of nutrition habits on the inflammatory processes of bowel, the main goal of this study was to evaluate the level of fecal Calprotectin in healthy subjects in Iranian army personnel that have specific and the same nutrition habits, in comparison with non-military population and also make this test an in-house method in Army laboratories. In this study a prospective and sample collection method used available samples (Convenience sampling). We collected stool samples from 108 subjects from Army personnel and 108 samples from non-military Iranian population with corresponding data collection form. Determination of Calprotectin levels was done by specific third generation quantitative ELISA method and statistics were done using SPSS software.The results showed that mean Calprotectin level in two included groups were 26.1 micrograms per gram in Army personnel group and 25.4 micrograms per gram in non-military control subjects. Fecal Calprotectin level in two studied groups wasn’t significantly different. Despite the little increase in Calprotectin levels in Army personnel group compared with control group this difference wasn’t statistically significant (P>0.05). We can conclude that the nutrition habits of army personnel could cause effects on inflammatory processes in digestive system. Determination of fecal Calprotectin levels as a cost effective and non invasive test could be used by military physicians for early diagnosis of inflammation in personnel by routine tests subjects.